A systematic review of studies on freshwater lakes of Ethiopia - Getaneh, Yonas; Abera, Wuletawu; Abegaz, Assefa; Tamene, Lulseged D. (Elsevier, 2022)
Study Region: The study covers the freshwater lakes of Ethiopia, which constitute about 87 billion cubic meters of water volume. The lakes are facing continued ecosystem degradation threats. Study Focus: The aim of this study was to make an inventory of existing literature regarding the freshwater lakes of Ethiopia and identify gaps and priorities for future research directions. This was done through a systematic review of published scientific literature related to the lakes and characterizing each study based on different criteria. New Hydrological Insights for the Region: We found a total of 231 articles on freshwater lakes of Ethiopia published in peer-reviewed journals between 1930 and March 2021. Most studies were focused on hydrochemical and biological characteristics of lakes, with less attention to physical structure and processes (including siltation, lake morphometry and catchment biophysical characteristics). Furthermore, (a) less attention was given to the spatial and temporal dynamics of variables that affect the freshwater lakes, (b) there was limited linkage between landscape hy drological dynamics and freshwater lakes and (c) the smaller highland lakes were given limited attention. Future research should be oriented to the study of the relationship between catchment biophysical dynamics and lake hydrological characteristics.